A Comprehensive Review on the Genetic Regulation of Cisplatin-induced Nephrotoxicity - Herrera-Pérez, Zeneida; Gretz, Norbert; Dweep, Harsh (Current genomics, 2016)
Cisplatin (CDDP) is a well-known antineoplastic drug which has been extensively utilized over the last decades in the treatment of numerous kinds of tumors. However, CDDP induces a wide range of toxicities in a dose-dependent manner, among which nephrotoxicity is of particular importance. Still, the mechanism of CDDP-induced renal damage is not completely understood; moreover, the knowledge about the role of microRNAs (miRNAs) in the nephrotoxic response is still unknown. miRNAs are known to interact with the representative members of a diverse range of regulatory pathways (including postnatal development, proliferation, inflammation and fibrosis) and pathological conditions, including kidney diseases: polycystic kidney diseases (PKDs), diabetic nephropathy (DN), kidney cancer, and drug-induced kidney injury. In this review, we shed light on the following important aspects: (i) information on genes/proteins and their interactions with previously known pathways engaged with CDDP-induced nephrotoxicity, (ii) information on newly discovered biomarkers, especially, miRNAs for detecting CDDP-induced nephrotoxicity and (iii) information to improve our understanding on CDDP. This information will not only help the researchers belonging to nephrotoxicity field, but also supply an indisputable help for oncologists to better understand and manage the side effects induced by CDDP during cancer treatment. Moreover, we provide up-to-date information about different in vivo and in vitro models that have been utilized over the last decades to study CDDP-induced renal injury. Taken together, this review offers a comprehensive network on genes, miRNAs, pathways and animal models which will serve as a useful resource to understand the molecular mechanism of CDDP-induced nephrotoxicity.